Multistability and hysteresis in states of oral microbiota: Is it impacting the dental clinical cohort studies?. (14th January 2023) - Mangal, Utkarsh; Noh, Kowoon; Lee, Seeyoon; Cha, Jae‐Kook; Song, Je Seon; Cha, Jung‐Yul; Lee, Kee‐Joon; Kim, Kwang‐Mahn; Kwon, Jae‐Sung; Choi, Sung‐Hwan
Abstract: Introduction: Microbiome from a "healthy cohort" is used as a reference for comparison to cases and intervention. However, the studies with cohort‐based clinical research have not sufficiently accounted for the multistability in oral microbial community. The screening is limited to phenotypic features with marked variations in microbial genomic markers. Herein, we aimed to assess the stability of the oral microbiome across time from an intervention‐free "healthy" cohort. Methods: We obtained 33 supragingival samples of 11 healthy participants from the biobank. For each participant, we processed one sample as baseline (T0) and two samples spaced at 1‐month (T1) and 3‐month (T2) intervals for 16S ribosomal RNA gene sequencing analysis. Results: We observed that taxonomic profiling had a similar pattern of dominant genera, namely, Rothia, Prevotella, and Hemophilus, at all time points. Shannon diversity revealed a significant increase from T0 ( p  < .05). Bray Curtis dissimilarity was significant ( R  = −.02, p  < .01) within the cohort at each time point. Community stability had negative correlation to synchrony ( r  = −.739; p  = .009) and variance ( r  = −.605; p  = .048) of the species. Clustering revealed marked differences in the grouping patterns between the three time points. For all time points, the clusters presented a substantially dissimilar set of differentially abundant taxonomic and functional biomarkers. Conclusion: Our observations indicate towards the presence of multistable states within the oral microbiome in an intervention‐free healthy cohort. For a conclusive and meaningful long‐term reference, dental clinical research should account for multistability in the personalized therapy approach to improve the identification and classification of reliable markers.